Relationship Of Insurance And Hospital Empathy With Satisfaction Of Return Interest In Outcoming Patients At Sundari Hospital - Dilla Fitria; Cut Saura Salmira; Aida Sulisna (Pena Cendekia Insani, 2022)
A level of patient feeling that arises as a result of the performance of health services obtained after the patient compares it with what he expects is patient satisfaction. To measure the quality of health services, the Serqual model or service quality is used as the basis for the research concept known as the Rater dimension. Where two of these dimensions are insurance and empathy in hospital health services. The purpose of this study was to be able to see the relationship between insurance and hospital empathy with satisfaction & interest in returning inpatients at Sundari Hospital. This study used a cross sectional approach with data collection using validated questionnaire data. The research sample was 68 people. The results showed that there was a significant relationship between the insurance variable and satisfaction & interest in revisiting with the results of p-value 0.007 <0.05, this value indicates that there is a relationship between the assurance variable on satisfaction and interest in revisiting general outpatients in Sundari Hospital. Meanwhile, for empathy, there is a significant relationship between the empathy variable with satisfaction and interest in revisiting with a p-value of 0.000 <0.05, this value indicates that there is a relationship between the empathy variable on satisfaction and interest in revisiting general outpatients at Sundari General Hospital. . Suggestions for hospitals to be able to conduct regular training related to communication management and education for all services.